COMPLICATIONS OF CHRONIC TOTAL OCCLUSION PERCUTANEOUS CORONARY INTERVENTION (Vietnam Journal of Community Medicine, 2022)
Background: Percutaneous coronary intervention (PCI) of chronic total occlusion (CTO) lesionscontinues to be a challenge, with a lower success rate and a higher risk of procedure-relatedcomplications than intervention on non-chronic total occlusion lesions. Due to a paucity of data onthis phenomena in Vietnam, we undertook this study to learn more about the complications associatedwith this complicated technique.Objectives: Determining the rate and factors associated with procedural complications of CTO-PCI.Subject – Method of Study: Observational study on eligible patients undergone percutaneouscoronary intervention for CTO lesions at the Ho Chi Minh City University Medical Center, Vietnam,from April 2017 to June 2019.Results: There were 194 CTO patients undergone percutaneous coronary intervention that wereenrolled in this study. The mean age was 67.3±11.3, in which male accounted for 73.7%. Comorbidities were hypertension (82.5%), old myocardial infarction (26.3%), previous PCI (26.3%),diabetes mellitus (29.9%), chronic kidney disease (9.8%). There were 77.4% patients hospitalizedfor acute coronary syndrome. Mean SYNTAX I score was 21.7±7.2, mean J-CTO score was 2.4±1.1.Antegrade intervention strategy accounted for 83.0%, with LAD being the most intervened lesion(55.7%). The overall success rate of the procedure was 87.1%. In-hospital procedural complicationsnoted in 16 cases (8.2%), included: coronary artery perforation (2.1%), coronary artery dissection(1.5%), side-branch loss (1.0%), thrombosis (1.0%), procedure-related myocardial infarction (0.5%),arrhythmia (1.5%), bleeding (0.5%). Factors related to procedural complications included: old age,previous PCI.Conclusion: Our study showed a low rate of CTO-PCI related procedural complications (8.2%).Factors related to high complication risk were old age and previous PCI
Keywords: Complications, pertacuneous coronary intervention, chronic total occlusion, antegrade, retrograde.